الإطار النّظري للعلاقة بين الحوكمة والأداء المالي للبنوك - حبيب, كريمة (جامعة الوادي - University of Eloued, 2016)
يهدف البحث لتسليط الضّوء على العلاقة بين تطبيق آليات حوكمة الشركات في المؤسسات المصرفية والأداء المالي للبنوك من خلال مختلف الدراسات النّظرية والتجريبية التي تناولت الموضوع. وذلك بغية الوقوف على مدى فعالية آليات الحوكمة ومدى قدرتها على تخفيف مشاكل الوكالة في المؤسسات المصرفية التي تتميز بتعدد أصحاب المصالح وطبيعة نشاطها المختلف عن بقية الشركات. وقد خلص البحث أن فعالية آليات حوكمة الشركات في البنوك تتأثر إلى حد كبير بمقدار السمات المحددة للبنوك، وهي المستويات العالية من الرفع المالي، الغموض، وكثرة اللّوائح التّنظيمية. ويختلف تأثيرها حسب نماذج تطبيق حوكمة الشركات في العالم. The research aims to shed light on the relationship between the application of corporate governance mechanisms in banking institutions and financial performance of banks through various theoretical and experimental studies on the subject. In order to stand on the effectiveness of governance mechanisms and the extent of its ability to mitigate the agency problems in the banking institutions, which is characterized by the multiplicity of stakeholders and the nature of its activity is different from the rest of the companies. The research concluded that the effectiveness of corporate governance mechanisms in banks affected to a large extent by specific features of the banks, the high levels of leverage, the opaquenes, and the large number of regulations. The impact varies depending on the application of corporate governance in the world models
مقال
Keywords: حوكمة الشركات ، الأداء المالي، الغموض; corporate governqnce, financial performance, opaqueness